Note rate modifications and subprime default rates (2009)
An important instrument to mitigate credit losses is modification of note rates of distressed borrowers. From a logistic model of early default, this article inferred the note rate impact on loan default probabilities, while controlling for loan characteristics (credit quality) and borrower location.